Abstract 042: Cognitive outcomes in patients with carotid insufficiency after undergoing direct extracranial‐intracranial bypass - Michael T. Bounajem; Robert C. Rennert; Allison Liang; Karol Budohoski; Craig J. Kilburg; Vivek Reddy; Jennifer Majersik; William Couldwell; Ramesh Grandhi (Stroke: Vascular and Interventional Neurology)
Introduction Extracranial‐intracranial (EC‐IC) bypass is a niche procedure that has been selectively used for flow augmentation or flow restoration in patients with intracranial carotid insufficiency.1 The underlying etiology varies but is most commonly related to Moya Moya disease (MMD) or intracranial carotid atherosclerotic disease (ICAD).2 Patients are often managed non‐operatively until they begin to develop symptoms such as transient ischemic attacks (TIAs) or strokes that are recalcitrant to maximal medical management, at which point bypass is pursued.1 This lag period, however, could put patients at risk for long term deficit, not only in the form of focal neurological deficits but also in terms of overall neurocognitive capability.3 Several reports have previously demonstrated some level of association between EC‐IC bypass and neurocognitive outcomes, though in isolated populations of either MMD or ICAD.4,5 We therefore aim to further assess the relationship between EC‐IC bypass and neurocognitive outcomes in patients with intracranial carotid insufficiency. Methods Patients ages 18 years and up undergoing EC‐IC bypass were identified from a single institution database between January 2020 and December 2021. Patient records were reviewed for demographic data including age and sex, as well as preoperative clinical information including comorbidities, operative indication, anticoagulation/antiplatelet therapy usage, prior ischemic stroke, modified Rankin score (mRS), and Montreal Cognitive Assessment (MOCA) score. Radiographic data was also collected including Suzuki grade, collateralization, and perfusion. Post‐operative clinical information including complications, discharge mRS, and discharge MOCA scores were identified. Follow‐up duration, MOCA scores, and mRS were also identified and recorded. Results Of the forty‐four patients that underwent EC‐IC bypass during the specified period, ten had cognitive assessments before and after surgery available for review. The indications for bypass in these cases were ICA steno‐occlusive disease resulting in strokes despite maximal medical management in 9 cases, and MMD in one case. Suzuki grade was IV in the MMD case. Pial collaterals were present in 7 cases, and ECA collaterals were present in 5. Prior ischemic strokes were present in 8 cases, with a preoperative mRS range from 1‐4 (median 1), and average MOCA of 20. Perfusion imaging demonstrated a Tmax mismatch in eight cases, with an average volume of 73.6 cc at risk. All patients underwent direct superficial temporal artery to middle cerebral artery bypass, with additional encephaloduroarteriomyosynangiosis (EDAMS). Follow up MOCA score was improved in 8 cases, unchanged in one case, and worsened in one case (average MOCA increased from 20 to 23). Follow up mRS ranged from 0‐2. Additionally, CT perfusion demonstrated notable improvements in Tmax >4 seconds (decrease from 176 cc to 110 cc), Tmax >6 seconds (decrease from 59 cc to 29 cc), and mismatch (decrease from 59 cc to 17 cc) at 6 month follow up. Conclusion Patients with carotid insufficiency from MMD or ICAD undergoing EC‐IC bypass demonstrate well below normal preoperative MOCA scores. This is suggestive of ongoing neurocognitive decline, which is an often overlooked issue in patients with these pathologies. MOCA and mRS both appear to improve in patients after bypass at longer term follow‐up, suggesting that bypass may be an effective method of addressing the issue of neurocognitive decline in patients with carotid insufficiency.